Bilateral ptosis as first presentation of cytophagic histiocytic panniculitis: a case report - Wang Liao; Songhua Xiao; Juanjuan Yong; Shengnuo Fan; Wenli Fang; Yuqiu Zheng; Jun Liu (BMC Ophthalmology, 2017)
Abstract Background Cytophagic histiocytic panniculitis (CHP) is a rare form of nodular panniculitis that may progress to panniculitis-like T-cell lymphoma. We report a case of CHP that first manifested as bilateral ptosis, which is the first reported case of this presentation. Case presentation A 25-year-old woman without medical history was referred to the neurology department of our hospital for evaluation of bilateral ptosis. Three months previously, she suddenly complained of bilateral ptosis without apparent cause. Simultaneously, non-painful tender subcutaneous nodules and eschar-like skin lesions were observed on her extremities and trunk. A diagnosis of CHP was made based on skin biopsy from the left thigh showing lobular panniculitis, vasculitis, and adiponecrosis, with infiltration of inflammatory cells, including lymphocytes, histiocytes, and phagocytic histiocytes. Her condition continued to worsen with corticosteroid and immunosuppressive agent (thalidomide) treatment. Significant improvement was noticed after three cycles of chemotherapy of THP-COP (pirarubicin, cyclophosphamide, vincristine, and prednisolone). Conclusions CHP is a rare condition whose clinical presentation may include bilateral ptosis and biopsy is required for diagnosis of CHP.